Los límites de la colaboración: dilemas metodológicos en un proyecto de investigación conjunto de israelíes y palestinos - WEIL, Shalva (Revista de Antropología Social, 2010)
This paper describes a collaborative study run by two researchers, one Palestinian and the other Israeli, who documented a project entitled: Curbing the Violence in Schools, in which Palestinian and Israeli school principals met during 2006–7 to discuss violence in their respective schools. The paper focuses upon the methodological dilemmas in joint anthropological research in a conflict situation, and particularly highlights the issues of power and equality, which may mirror Palestinian–Israeli realities. While the project and the research were run equally on both sides, collaboration was shown to have its limits, although the study promoted proactivism. This is in line with Lassiter’s claim (2005) that collaborative ethnography has the capacity to advance a public anthropology.
Keywords: Methodology; Palestinians; Israelis; Collaboration; Proactivism; Violence